PENERAPAN PROGRAM POJOK BACA SEBAGAI SARANA LITERASI MEMBACA ANAK DI DESA KLUMPANG KAMPUNG - Chuzaimah Batubara; Nabila Nabila; Muhammad Daffa Raihan; Muhammad Naufal Habibi; Miftahul Jannah; Nairah Al zany; Amanda Alia Misara Ginting; Nadia Nadia; Canda Wulandari; Fadilah Aulia; Khaira Fahzira (STAI Darul Qalam Tangerang, 2025)
This community service program (KKN) is carried out as a manifestation of the student's real work program (KKN) in the form of an effort to implement the reading corner program as a means of children's reading literacy in Klumpang Village. This community service program organized by the State Islamic University of North Sumatra Medan has the motto: strengthening the role of universities to realize a progressive society and have Islamic values. This program is carried out for 30 days or precisely from mid-July to August 2025. This program tries to solve problems regarding reading literacy in children in Klumpang Village through a reading corner. The method used in this community service is qualitative with a community approach. The output of this program is the realization of a reading corner that is pleasant and comfortable for children. Klumpang Village in developing their reading literacy skills.